Language Variation Used by Food Vloggers on TikTok and Its Influence on Audience Language Use - Mutia Putri; Sholihatul Hamidah Daulay (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates language variation employed by food vloggers on TikTok and examines its subsequent influence on how audiences communicate in digital spaces. As short-form video content continues to reshape sociolinguistic norms among Indonesian youth, food vloggers have emerged as influential language agents who blend Bahasa Indonesia with English, deploy culinary-specific slang, and adopt trending expressions that resonate with younger audiences. Drawing on a qualitative descriptive approach, this research collected data from TikTok food vlogs, including video transcripts, captions, comments, and hashtags, from five prominent Indonesian food vlogger accounts throughout 2023 to 2024. The analysis was guided by sociolinguistic frameworks proposed by Labov (1972), Hymes (1974), Fishman (1972), and Trudgill (2000). Findings reveal four dominant patterns of language variation: code switching between Bahasa Indonesia and English, code mixing within single utterances, the use of culinary slang, and the appropriation of prestige language to construct social identity. Expressions such as "worth it," "creamy banget," "hidden gem," and "healing sambil ngopi" are not merely descriptive but serve as markers of modern, globally-oriented identity. Audience analysis further shows that followers increasingly replicate these linguistic patterns in their comment sections, suggesting a significant bidirectional influence between content creators and viewers. This study contributes to growing scholarly interest in digital sociolinguistics, youth language, and the role of social media influencers in shaping communicative norms.